PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV DI SD NEGERI 31 BANDA ACEH - Sy. Najwa Hanum Najwa; Intan Safiah; Hasniyati (LPPM Universitas Cipta Mandiri, 2025)
This purpose of the study is to determine the influence of the Cooperative Integrated Reading and Composition (CIRC) learning model on Indonesian language learning outcomes. The research used a quantitative approach with an experimental design and involved fourth-grade students at SD Negeri 31 Banda Aceh as subjects. The sample consisted of two classes: an experimental class that used the CIRC model and a control class that used conventional learning. Data were collected through pretest and posttest and analyzed using normality, homogeneity, Wilcoxon, and Mann-Whitney tests.The results show that the CIRC learning model significantly influences improving students' learning outcomes in identifying main ideas and comprehending the content of a text. This is evidenced by a p-value of less than 0.05 on the Wilcoxon test, which indicates a significant difference between the pretest and posttest scores of the experimental group, with an Asymp. Sig. (2-tailed) value of 0.000 (0.000 < 0.05). Furthermore, a Z-value of -4.139 suggests that the posttest scores of the control group also showed a significant increase compared to their pretest scores. The Mann-Whitney test also revealed a significant difference in learning outcomes between the experimental and control groups.Based on these findings, the CIRC learning model is proven to be more effective in improving the Indonesian language learning outcomes of fourth-grade students at SD Negeri 31 Banda Aceh compared to conventional learning models.